1991
DOI: 10.1152/jappl.1991.71.3.910
|View full text |Cite
|
Sign up to set email alerts
|

Elevated interstitial fluid volume in rat soleus muscles by hindlimb unweighting

Abstract: Hindlimb unweighting is a commonly used model to study skeletal muscle atrophy associated with disuse and exposure to microgravity. However, a discrepancy in findings between single fibers and whole muscle has been observed. In unweighted solei, specific tension deficits are greater in whole muscle than in single fibers. Also, metabolic enzyme activity when normalized per gram of mass is depressed in whole muscle but not in single fibers. These observations suggest that soleus muscle interstitial fluid volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…For example; the soleus muscle wet weight was 56% of control while the soleus slow fibres were 44% of control, the plantaris muscle wet weight was within control range while the plantaris fast fibres were 70% of control values. These differences may be due to an increase in the interstitial fluid of the muscle (Kandarian et al, 1991) and/or an increase in the amount of muscle connective tissue (Hauschka et al, 1987), both of which have been reported following suspension. Because of such changes, the whole muscle wet weight will not accurately reflect the degree of atrophy in the individual fibres.…”
Section: Discussionmentioning
confidence: 95%
“…For example; the soleus muscle wet weight was 56% of control while the soleus slow fibres were 44% of control, the plantaris muscle wet weight was within control range while the plantaris fast fibres were 70% of control values. These differences may be due to an increase in the interstitial fluid of the muscle (Kandarian et al, 1991) and/or an increase in the amount of muscle connective tissue (Hauschka et al, 1987), both of which have been reported following suspension. Because of such changes, the whole muscle wet weight will not accurately reflect the degree of atrophy in the individual fibres.…”
Section: Discussionmentioning
confidence: 95%
“…Increased extramyocyte space with aging may be caused by increased connective tissue, increased fat, and increased fluid volume in both rodents and humans (Hatakenaka et al, 2001;Kandarian et al, 1991;Lexell et al, 1988;Payne et al, 2003). While increased connective tissue, water, and fat are all potential contributors in increased extramyocyte space, the large degree (3.9 fold) of elevated extramyocyte space in OAL compared with YAL suggests a potential contribution of connective tissue including the endomysium and perimysium.…”
Section: Discussionmentioning
confidence: 99%
“…PLAN) versus dorsiflexor muscles (e.g. EDL) [Riley et al, 1990a;Steffen et al, 1990;Diffee et al, 1991;Kandarian et al, 1991;Apseloff et al, 1993;Stump et al, 1997;Thompson et al, 1998]. Younger animals appear to have faster rates of atrophy in response to HLS.…”
Section: Effects Of Hindlimb Suspension In Mature Male Ratsmentioning
confidence: 99%